2018
DOI: 10.1186/s11658-017-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered endoxifen inhibits tumor growth in melanoma-bearing mice

Abstract: Endoxifen, an active metabolite of tamoxifen, has been shown to be an effective anti-estrogenic agent in estrogen receptor-positive breast cancer patients. In melanoma, estrogen receptor expression is shown to be associated with disease progression. However, the therapeutic benefit of endoxifen in melanoma has not yet been evaluated. Here, we present the first demonstration of the anti-melanogenic activity of endoxifen in vitro and in vivo.The in vitro cytotoxic effect of endoxifen was tested using a cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…It has recently been demonstrated that endoxifen, a 100-times more powerful active metabolite compared to TAM, can be a promising new therapeutic agent against CM by blocking ER transcription [40]. The mechanism of action of endoxifen inhibition in CM cells has been not completely clarified, but at nanomolar concentrations, the molecule can effectively block ER transcriptional activity, resulting in anti-melanogenic activity [40]. Besides, the selective ERβ agonist LY500307 has been observed to be effective against lung metastasis from CM, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that endoxifen, a 100-times more powerful active metabolite compared to TAM, can be a promising new therapeutic agent against CM by blocking ER transcription [40]. The mechanism of action of endoxifen inhibition in CM cells has been not completely clarified, but at nanomolar concentrations, the molecule can effectively block ER transcriptional activity, resulting in anti-melanogenic activity [40]. Besides, the selective ERβ agonist LY500307 has been observed to be effective against lung metastasis from CM, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…injected with melanoma cells, decreases lung nodules [55]. Oral administration of TAM [56] and EDX [57] exert inhibitory effects on tumor metastatization into the mouse lungs. (Right) AR action is responsible for the increased number of lung metastases through the miR-539-3p/USP13/MITF/AXL axis [58], whereas AR blockade mediates an increase in the immune response [59].…”
Section: Female Hormone Activitymentioning
confidence: 99%
“…Therefore, to induce melanoma cell death in vitro, endoxifen (EDX), a metabolite of TAM that is safer and has more cytostatic activity than the parent drug has been used [66]. Furthermore, EDX orally administered in mice for four weeks reduced lung metastatic nodules without any side effects [57]. Another reason for different epidemiological evidence in TAM's effectiveness could lie in its possible different and tissue-related effects on the two estrogen receptors, similarly to E2 [67,68].…”
Section: Female Hormone Activitymentioning
confidence: 99%
“…It has been found to be up to 100 times more potent than TAM but with a more favorable toxicity and safety profile. For all these reasons endoxifen could be a promising new therapeutic agent for advanced melanoma [84]. Selective pharmacological activation of ERβ through its agonist LY500307 has been shown to have a potent suppressive action against lung metastasis from melanoma in vitro and in vivo.…”
Section: Present and Future Perspectivesmentioning
confidence: 99%